Practical Example of Introductory Engineering Education Based on the Design Process and Teaching Methodology Using a Gyro Bicycle - HIGA, Yoshikazu; SHIMOJIMA, Ken (Asian Journal of Education and Training, 2018)
This report describes a workshop on the Dynamics of Machinery based on the fabrication of a gyro- bicycle in a summer school program for junior high school students. The workshop was conducted by engineering students who had completed “Creative Research”, an engineering design course at the National Institute of Technology, Okinawa College (Okinawa KOSEN). The paper reports on the approximately one month run-up to the workshop and describes the classroom scene on the day of presentation. At the close of the workshop, participants were asked to complete an evaluative questionnaire. Responses were quite positive with respect to the lecture slides, guidance and workshop content. On the instructor side, it was confirmed that to promote student understanding, communications and teaching skills are crucial, although it has a passive impression for the achievement level of the workshop.